Netflix as a Digital EFL Learning Aid for Vocabulary Improvement: College Students’ Perspective - Damanik, Ivana Jane; Katemba, Caroline Victorine (ETERNAL (English, Teaching, Learning, and Research Journal), 2021)
In the digital era, people use technology to expand the source of learning and teaching. To comprehend a general discussion at a native speaker level, one needs a vocabulary of thousands of words. This research seeks to find out college students’ perception about English movies/series in Netflix contribution as digital EFL learning aid on vocabulary improvement. The research questions of this study are: (1). What is the perspective between private university students and state university students towards Netflix as digital EFL learning? (2). Is there any significant difference between female and male students’ perspectives toward Netflix as digital EFL learning? (3). Are there any differences in the perspective about Netflix as a digital EFL learning based on their age? This study employed a qualitative method by giving an online questionnaire on Google Form. The questionnaire is distributed to students in various universities. The subject of this research is college students who are taking English classes. The findings of this study indicate that watching English movies/series on Netflix can help students improve their vocabulary.